Potential Antigenic Cross-reactivity Between Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Dengue Viruses. (14th August 2020) - Lustig, Yaniv; Keler, Shlomit; Kolodny, Rachel; Ben-Tal, Nir; Atias-Varon, Danit; Shlush, Ekaterina; Gerlic, Motti; Munitz, Ariel; Doolman, Ram; Asraf, Keren; Shlush, Liran I; Vivante, Asaf
Abstract: Background: Coronavirus disease 2019 (COVID-19) and dengue fever are difficult to distinguish given shared clinical and laboratory features. Failing to consider COVID-19 due to false-positive dengue serology can have serious implications. We aimed to assess this possible cross-reactivity. Methods: We analyzed clinical data and serum samples from 55 individuals with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. To assess dengue serology status, we used dengue-specific antibodies by means of lateral-flow rapid test, as well as enzyme-linked immunosorbent assay (ELISA). Additionally, we tested SARS-CoV-2 serology status in patients with dengue and performed in-silico protein structural analysis to identify epitope similarities. Results: Using the dengue lateral-flow rapid test we detected 12 positive cases out of the 55 (21.8%) COVID-19 patients versus zero positive cases in a control group of 70 healthy individuals ( P = 2.5E−5). This includes 9 cases of positive immunoglobulin M (IgM), 2 cases of positive immunoglobulin G (IgG), and 1 case of positive IgM as well as IgG antibodies. ELISA testing for dengue was positive in 2 additional subjects using envelope protein directed antibodies. Out of 95 samples obtained from patients diagnosed with dengue before September 2019, SARS-CoV-2 serology targeting the S protein was positive/equivocal in 21 (22%) (16 IgA, 5 IgG) versus 4 positives/equivocal in 102 controls (4%) ( P = 1.6E−4). Subsequent in-silico analysis revealed possible similarities between SARS-CoV-2 epitopes in the HR2 domain of the spike protein and the dengue envelope protein. Conclusions: Our findings support possible cross-reactivity between dengue virus and SARS-CoV-2, which can lead to false-positive dengue serology among COVID-19 patients and vice versa. This can have serious consequences for both patient care and public health. Abstract : Significant serologic cross-reactivity between dengue virus and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which can lead to false-positive dengue serology among coronavirus disease 2019 (COVID-19) patients and vice versa. Cross-reactivity between SARS-CoV-2 and dengue viruses may interfere with accurate clinical diagnosis and treatment of both diseases.